Reducing the Amount of Data for Creating Routes in a Dynamic DTN via Wi-Fi on the Basis of Static Data - Yulia Shichkina; Alexander Koblov (Journal of Computer Networks and Communications)
This article presents the results of research on the acceleration of data processing in the construction routing in dynamic DTN, realized through the devices established in moving objects and connected by means of Wi-Fi. The routes are constructed based on the prehistory of the movement of objects, which is stored in the database in the csv format. This database has a large volume and contains unnecessary and incorrect information. The article shows the possibility of speeding up the process of constructing routes using data precleaning. Reducing data volume is proposed by constructing an enlarged grid on the object movement map. This article also demonstrates the use of fuzzy logic and graph theory for constructing routes.